Badan Hukum di Langit Pendidikan (Studi Evaluasi Kebutuhan Satuan Pendidikan) - M. Kholid Fathoni (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2011)
The obligation of legal body upon every educational institution or its founder is still an unfinished law agenda of this country. Act No 20/2003 on National Education stated that the specific law on education legal body must be enacted. The government has released the law No 9/2009 about Legal Body of School and University, but the Council of Constitution has canceled it in 2010. If a new regulation on legal body will be initiated as law, instead of the cancelled one, the Government should be in alert and in full contemplation among critics, last mistakes, and wider community sounds so that can avoid obstacles. This research is important in accordance with Governmental planning when the body of education institution will be constructed as a legal entity. The sounds and documents which are collected from various forums in discussion of the topic will be analyzed as a research conclusion.Â ABSTRAKKetentuan tentang keharusan penyelenggara dan/atau satuan pendidikan berbentuk badan hukum pendidikan masih merupakan agenda hukum negeri ini. Pasal 53 UU Sisdiknas No.20/2003 mengamanatkan disusunnya suatu undang-undang tentang badan hukum pendidikan. Sebelumnya, UU No 9/2003 Tentang Badan Hukum Pendidikan sudah diterbitkan, namun oleh Mahkamah Konstitusi dinyatakan â€œtidak mengikatâ€ pada tangal 31 Maret 2010. Apabila â€œundang-undang baruâ€ akan disusun menggantikan UU No 9, maka diperlukan upaya Pemerintah agar benar-benar memperhatikan poinpoin penting penyebab pembatalan UU No 9 serta suara masyarakat secara lebih luas agar kelak tidak mengalami nasib UU No 9. Dengan cara melakukan analisis terhadap dokumen di berbagai forum pembahasan seputar permasalahan, penelitian ini dimaksudkan memetakan permasalahan badan hukum di bidang pendidikan. Penelitian ini dapat dimanfaatkan untuk membantu para pengambil kebijakan pendidikan mengetahui kebutuhan nyata para penyelenggara pendidikan di lapangan.